Slovenci v Avstriji kot eden prednostnih predmetov v slovenskih etničnih študijah - Stergar, Janez (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2004)
The research of recent (predominantly Slovenian, but also Austrian) historiographical and / or social scientific production on Carinthian Slovenians in crossborder ties between Slovenia and the Austrian federal province of Carinthia, or Austria - an issue that has traditionally belonged to the central themes of Slovenian history writing - has been a complementary part of the project on processes of ethnic differentiation in Slovenia. This unpublished contribution, which has in part already been presented at two conferences in Austria, contains information about the contents and the characteristics of an extensive collection of recent publications discussing the theme under scrutiny here. It also quotes some results from author's research into the biographies of representative personalities and historical evolution of central minority organisations of Carinthian Slovenians.
Keywords: Austria; Avstrija; zamejski Slovenci; Carinthian Slovenes; koroški Slovenci; narodne manjšine; mednarodni odnosi